THE EFFECT OF LOW-DOSE MOLASSES ADDITION ON WATER QUALITY AND BIOFLOCK FORMATION IN CATFISH (Clarias gariepinus) CULTURE - Dwita Nurphadilah; Azam Bachur Zaidy; Otie Dylan Soebhakti Hasan (Media Akuakultur, 2026)
Biofloc technology utilizes heterotrophic bacteria to control waste by adding organic carbon sources. The addition of organic carbon sources is based on the feed-to-carbon ratio. This study aims to evaluate the effect of adding low doses of molasses to a biofloc system on water quality and floc formation in catfish farming. The study used a Completely Randomized Design (CRD) with four treatments: no molasses (control), 5%, 10%, and 15% molasses, each with three replicates. The results showed that molasses addition had no significant (P > 0.05) effect on water quality and floc volume. Parameters such as temperature, pH, TSS, TAN, nitrite, and nitrate remained relatively stable across all treatments, while floc volume at 5%, 10%, and 15% molasses was relatively similar. Thus, the use of 5% molasses is recommended as the most efficient dose because it produces water quality and floc formation conditions equivalent to higher doses. The presence of plankton in the rearing medium and the fish intestines indicates that the flocs have the potential to be utilized as natural feed by catfish.